2021
DOI: 10.1111/febs.16053
|View full text |Cite
|
Sign up to set email alerts
|

Functional implications of residues of the B′ motif of geminivirus replication initiator protein in its helicase activity

Abstract: Geminivirus replication initiator protein (Rep) is a multifunctional viral protein required for replication. During the process of viral replication, Rep acts as a site-and strand-specific endonuclease, ligase, ATPase, and helicase. B' motif and b-hairpin loop of the geminivirus Rep are conserved and important for Rep-mediated helicase activity required for viral replication. To dissect the roles of various amino acid residues of the B' motif and b-hairpin loop of the geminivirus Rep helicase in its process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The motor function of Rep protein is driven by ATP hydrolysis activity of its C-terminal region. Recent studies have shown Lys-272 (Bʹ motif residue), Lys-286 and Asp-289 [27,43,44]. In the current study, the Rep protein region associated with the ATP hydrolysis and DNA unwinding function of the protein was found to be the region interacting with the βC1 protein.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The motor function of Rep protein is driven by ATP hydrolysis activity of its C-terminal region. Recent studies have shown Lys-272 (Bʹ motif residue), Lys-286 and Asp-289 [27,43,44]. In the current study, the Rep protein region associated with the ATP hydrolysis and DNA unwinding function of the protein was found to be the region interacting with the βC1 protein.…”
Section: Discussionmentioning
confidence: 52%
“…The motor function of Rep protein is driven by ATP hydrolysis activity of its C-terminal region. Recent studies have shown Lys-272 (Bʹ motif residue), Lys-286 and Asp-289 (hairpin loop residues), Lys-227 (Walker-A residue), and Asp-261 and Asp-262 (Walker-B residues) to be the crucial amino acid residues for Rep protein function [9–11, 27]. The residues involved in ATP hydrolysis, DNA binding and DNA helicase function of Rep protein are conserved across the super family 3 (SF3) helicase members [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coordinates of the oligomerization domain and RETINOBLASTOMA protein interaction surface are inferred based on alignment to the Rep protein sequence from tomato golden mosaic virus (Orozco and Hanley-Bowdoin 1998, Kong et al 2000, Reyes 2012). Walker motifs were inferred based on Ruhel et al (2021). Positions of amino acids L145 and E176 are shown with a purple line and a blue line.…”
Section: Introductionmentioning
confidence: 99%